Penerapan Model Pembelajaran Think Talk Write (TTW) dalam Meningkatkan Hasil Belajar Bahasa Indonesia Siswa Kelas Rendah SDI Asy Syarif Mojokerto - Anggara Dwinata; Eko Hardinanto; Emy Yunita Rahma Pratiwi (Karangan: Jurnal Bidang Kependidikan, Pembelajaran, dan Pengembangan, 2025)
This study is an effort to improve student learning outcomes in the Indonesian language subject through the application of the Think Talk Write (TTW) learning model to lower grade students at SDI Asy Syarif Mojokerto. This study was motivated by low student learning outcomes and below the KKM in the Indonesian language subject. The research method used was classroom action research (PTK). The research sample was conducted randomly with a total of 30 students. Data analysis used quantitative data with percentage increase techniques. The results of the study showed that student learning outcomes increased quite significantly in cycle 1 by 40% and cycle 2 by 67%. This provides significant evidence that the application of the Think Talk Write (TTW) learning model can improve the learning outcomes of lower grade students at SDI Asy Syarif Mojokerto.